SCANNING LASER POLARIMETRY IN THE DIAGNOSIS OF GLAUCOMA - Barbara Cvenkel (Zdravniški Vestnik, 2004)
Background. Retinal nerve fibre layer (RNFL) loss is an early sign of glaucoma and may precede the optic disc damage and visual field loss. Scanning laser polarimetry (SLP) is a quantitative method measuring the RNFL thickness surrounding the optic disc. The instrument (GDx, Laser Diagnostics Technologies, San Diego, CA) uses a near-infrared diode polarized light which by passing through the birefringent RNFL undergoes a change of polarization (i. e. retardation). The resulting phase shift (retardation) is related to the thickness of the RNFL. The method is used primarily in the diagnosis of glaucoma, but it is also helpful in assessment of the RNFL in optic neuropathy of different etiopathogenesis. Conclusions. In the article we presented the results of SLP in a healthy subject and in glaucoma patients with different stages of the disease. In the diagnosis of early and moderate glaucoma SLP has low sensitivity and specificity and cannot substitute a thorough ophthalmologic examination. Nevertheless, it provides additional information to our management of glaucoma patients.